Temperature distribution of brine and gas in the tubing during debrining of a salt cavern gas storage. (June 2022) - Xie, Dongzhou; Wang, Tongtao; Li, Long; He, Tao; Chai, Guoxing; Wang, Duocai; Zhang, Hong; Ma, Tieliang; Zhang, Xin
Highlights: A mathematical model is built to calculate the temperature distribution of brine and gas in the tubing during debrining. A finite element iterative method is proposed to solve the mathematical model. The temperature distribution of brine and gas in the tubing during debrining is calculated. Influencing factors of brine temperature in the tubing during debrining are discussed. The method of calculated salt crystal growth is proposed. Abstract: During the debrining of an underground gas storage salt cavern (UGS), the decrease of brine temperature may cause the debrining inner tubing (DIT) to be blocked by salt crystal separating from brine. In this paper, a mathematical model used to calculate the temperature distribution of brine and gas in the tubing during the debrining is built based on the theories of heat transfer. A finite element iterative method is used to solve the mathematical model. A-1 cavern of Jintan UGS is taken as an example. The temperature distribution of brine and gas is calculated under different DIT sizes and debrining rates based on the mathematical model. The results show that the gas temperature increases rapidly in the 0∼-30m and slowly in -30 ∼ -925 m. Increasing DIT size and debrining rate have no significant effect on the gas temperature distribution. The brine temperature decreases non linearly with decreasing depth. The brine temperature increases with the increase of debrining rate and decrease of DIT size. Brine temperature falls slowly over the range from -925 m to -600 m, and significantly above -600 m. Increasing debrining rate and decreasing thermal conductivity of tubing can decrease the drop of brine temperature. Increasing gas injection temperature has a minor effect on the brine temperature distribution. In order to prevent the DIT blocking by salt crystal, we proposed that use a DIT with low thermal conductivity to debrine. The accuracy and reliability of the model are verified by comparing the calculated values of brine temperature at the wellhead with field measured values for an actual cavern debrining. This study provides a theoretical basis for evaluating the temperature distribution of brine and predicting salt crystal growth during debrining.